The Influence of Career Development and Work Motivation on Employee Performance With Job Satisfaction as an Intervening Variable at PT PLN (Persero) S2JB Distribution Parent Unit - Lestari, Tiara Ayu; Adam, Mohamad; Zunaidah, Zunaidah; Hanafi, Agustina; Wita Farla WK (SEAN Institute, 2024)
This research aimed to examine the influence of career development and work motivation on employee performance with job satisfaction as an intervening variable. This research uses a quantitative approach method. The sample in this research was employees of PT PLN (Persero) S2JB Main Distribution Unit, with a total of 128 respondents. The research data source was primary data by distributing questionnaires. The data analysis method in this research uses Structural Equation Modeling (SEM) with the SmartPLS application. The results of this research show that the career development variable has a significant positive effect on employee performance, work motivation has a significant positive effect on employee performance, career development has a positive effect on job satisfaction, work motivation has a positive effect on job satisfaction, job satisfaction has a positive effect on employee performance. Apart from that, career development has a positive and significant effect on employee performance which is mediated by job satisfaction and work motivation has a significant positive effect on employee performance which is mediated by job satisfaction.